Social business in online financing: Crowdfunding narratives of independent documentary producers in Turkey. (February 2015) - Koçer, Suncem
Crowdfunding is a relatively novel concept in Turkish public discourse. Yet, activist media producers in Turkey actively use online opportunities to solicit production, post-production and distribution financing. This article explores crowdfunding as a signifier that draws public attention to media texts for which online funding drives are performed. As crowdfunding campaigns circulate through social media, they forge publics around the related films, videos, stories and, more significantly, the social causes around which these media revolve. Based on long-term ethnographic research with independent media producers in Turkey, the article scrutinizes the crowdfunding adventures behind three documentaries, My Child, Ecumenopolis and I Flew You Stayed, as narrated by their producers. Using the analysis of the campaigns for these documentary films as cases, I argue that in addition to being a means to raising funds, crowdfunding is a tool to accomplish social and political ends ranging from creating communities of support and attracting media attention to building a reputation of independence.